The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1055/s-0039-1695009
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Reticulated Platelets Reveals a Prothrombotic Profile

Abstract: Reticulated platelets (RPs) are larger, hyperreactive platelets that contain significantly more ribonucleic acid (RNA) compared with mature platelets (MPs). High levels of RPs in peripheral blood are predictors of an insufficient response to dual antiplatelet therapy in cardiovascular patients and of adverse cardiovascular events. However, the mechanisms underlying these correlations remain widely unknown and the biology of RPs has not been investigated yet. Here, we compared for the first time the transcripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 83 publications
1
74
0
Order By: Relevance
“…Peripheral venous blood was collected in citrate tubes and immediately processed to produce platelet-rich plasma (PRP) as described before 25,26 . CyTOF staining assay was performed according to the manufacturer's protocols.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…Peripheral venous blood was collected in citrate tubes and immediately processed to produce platelet-rich plasma (PRP) as described before 25,26 . CyTOF staining assay was performed according to the manufacturer's protocols.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…Another mechanism for increased platelet reactivity is an increased relative number of so-called reticulated platelets, young platelets that contain more αand dense granules and mitochondria and have an increased reactivity compared with older platelets [75,76]. A recent study in mice indicated that high glucose levels led to increased platelet production by the bone marrow megakaryocytes, with the circulating platelets having a high fraction of reticulated platelets [77].…”
Section: Platelet Hyperreactivity As Risk Factor For Atherosclerotic mentioning
confidence: 99%
“…87 In humans, the analysis of reticulated platelets revealed overlapping findings with large platelets. Both subpopulations contain higher amounts of RNA including transcripts for prohemostatic proteins 63,88 and show more P-selectin expression and PS-exposure compared to mature ones after activation. 15,89 Reddy et al also found reticulated human platelets being larger and more prone to expose PS, 90 but a similar size and PS exposure in young and old rabbit platelets distinguished by a biotinylation approach, solidifying differences between species.…”
Section: Are L Arg E Pl Atele Ts Re Ti Cul Ated?mentioning
confidence: 99%